So say the little monkeys - Van Laan, Nancy; Heo, Yumi (New York : Atheneum Books for Young Readers, 1998)
A rhyming retelling of an Indian folktale from Brazil about tiny, playful monkeys and why they have no place to call home.
"An Anne Schwartz book.".
Keywords: Indians of South America -- Brazil -- Folklore; Tales -- Brazil; Monkeys -- Brazil -- Folklore; Indians of South America -- Brazil -- Folklore; Monkeys -- Folklore; Folklore -- Brazil; Tales -- Brazil; Indians of South America; Monkeys -- Folklore; Folklore -- Brazil